Thermal effects in 1.3-μm InAs/GaAs quantum-dot vertical-cavity surface-emitting lasers - Xu, Dawei (2011)
The goal of this project is to analyze and characterize the influence of self-heating on the output performance in 1.3-μm GaAs/InAs quantum-dot (QD) vertical-cavity surface-emitting lasers (VCSELs) and to realize improvement and optimization in device fabrication. This research work includes both theoretical (modeling) and experimental (device processing) approaches. In theoretical study, a self-consistent model comprised of rate equations and the thermal conduction equation was established to analyze the influence of self-heating on the carrier occupation, the quantum efficiency and the output power of 1.3-μm QD VCSELs. The devices with both single- and multi-mode emission were fabricated and characterized. The influence of self-heating was characterized based on the combination of theoretical and experimental investigations. The dielectric-free approach and the surface-relief technique were adopted to improve output power and the fundamental-mode emission, respectively. These were both realized in the QD VCSEL for the first time.